2007
DOI: 10.1080/07399330601128445
|View full text |Cite
|
Sign up to set email alerts
|

Survivor Dragon Boating: A Vehicle to Reclaim and Enhance Life After Treatment for Breast Cancer

Abstract: The authors investigated the psychosocial impact of dragon boat participation on women who have been treated for breast cancer. Open-ended qualitative interviews were completed by 10 new members recruited from two breast cancer survivor dragon boat teams. Our findings indicate that the women's experience of survivor dragon boating surpassed their expectations and offered them hope and increased strength and the ability to regain control of their lives. Key themes emerging from the in-depth interviews that enca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 29 publications
2
45
0
Order By: Relevance
“…The participants in our study also reported that exercise was a distraction from a stressful cancer experience. Previous research indicates that women with breast cancer find exercise to be a positive element providing them with a break from the illness 22,31,32 . Mackey Physical activity as a coping strategy in women with breast cancer has been described previously as a way of dealing with difficult emotions 34 and in this way contributes to psychological wellness 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The participants in our study also reported that exercise was a distraction from a stressful cancer experience. Previous research indicates that women with breast cancer find exercise to be a positive element providing them with a break from the illness 22,31,32 . Mackey Physical activity as a coping strategy in women with breast cancer has been described previously as a way of dealing with difficult emotions 34 and in this way contributes to psychological wellness 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Both men and women of varying fitness levels and with no previous experience can participate. Thus far, dragon boating is the only team-based physical activity program studied in cancer survivors, but none of these earlier studies included a comparison group [7,10,[12][13][14].…”
Section: Introductionmentioning
confidence: 98%
“…In 1996, Dr. Don McKenzie, MD, PhD, a sportsmedicine physician from Vancouver, Canada, formed the first all-breast-cancer-survivor dragon boat team, Abreast in a Boat, and demonstrated that strenuous, upper body exercise in the form of dragon boat training, a predominantly aerobic form of exercise, did not induce or exacerbate lymphedema symptoms [20]. Dragon boat training is now widely advocated as a safe and beneficial form of exercise for survivors of breast cancer [22].…”
Section: Introductionmentioning
confidence: 99%